Pakistan and the New Frontier of Cyber Diplomacy: Challenges and Strategic Opportunities - Habib Ur Rehman; Prof. Dr. Abdul Wadood (BTTN Journal, 2025)
This study examines cyber diplomacy as a strategic tool in the realm of contemporary international politics in the context of its importance for Pakistan amid the dynamic and growing cyber environment. With a qualitative and library-based research methods reinforced by real-life policy observation, this paper critically examines how cyber diplomacy can contribute to multi-stakeholder cooperation and norm development in cyberspace. It pinpoints Pakistan’s key challenges such as legal lacunas, underdeveloped cyber capacity and poor strategic communications but also opportunities in the areas of digital governance, economic growth and regional cooperation. The study recommends that there is a need for a unique cyber diplomacy division, robust legal underpinning, and mainstreaming of cyber strategies in Pakistan’s foreign policy objectives. Finally, the study adds to the nascent literature on non-conventional diplomacy by providing policy-relevant insights specific to Pakistan’s cyber future.